(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Cancer is a global leading cause of death which suffers from treatment failures mainly due to intensive toxicity and lack of effectiveness of conventional drugs. The application of nanotechnology in cancer treatment promises to overcome the limitations of conventional drugs/drug delivery systems and improve their therapeutic efficacy. Materials at the nano scale possess novel properties that have an impact on their biological behaviour. The physiological interactions of nanomedicines in the body, which differ from those of conventional medicines, may provide benefits in pharmaceutical and/or clinical applications including, improvements in solubility, stability, efficacy, reduction of side effects, prevention and treatment of diseases. This paper discusses the unique characteristics and distinguished advantages of nanomaterials as anticancer drug carriers. Physicochemical properties of nanomaterials are critical parameters to their clinical translation. Hence, the impact of the main physicochemical properties on the efficacy of anitcancer nanomaterials, which are found to effective for cancer treatment and/or diagnosis, are presented. It is important to have reliable and robust characterization techniques that could enable relate physicochemical properties of nanomaterials with their in vivo behaviour. Brief explanation of the different techniques that can be used for studying the different physicochemical characteristics of nanomaterials is given. An important consideration, to achieve fast and successful development of nanotechnology-based anticancer drug products, is assessment and optimization of physicochemical and biopharmaceutical properties at the early stage. Obviously this requires collaboration among the different discovery and development scientists.